ALQURAN, TAFSIR DAN FENOMENA SOSIAL KEMASYARAKATAN - Ritonga, Abdullah Sani (Universitas Islam Negeri Sumatera Utara, 2019)
The Koran, in a textual level, will not increase. However, contextually, that is through interpretation, its values continue to develop. These developments, one of which is to answer the social phenomenon that is constantly developing. Mufassir with a variety of methods have done that, one of which is, through a thematic approach where each verse of the Koran is then sought continuity between one another. This paper seeks to trace how existing sources discuss the matter above while hoping it will be developed. The basic aim is to make the Koran the key to progress and the foundation of goodness.